Children's Education According to the Al-Quran Perspective (Qs. Luqman Verse 12-19) - Wildan Solihin; Uus Husni Hoer; Helmi Muslimah; Surya Aspara (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
The educational messages given to Luqman by Allah are immortalized in the Quran as a lesson for future Muslims, because fundamentally, monotheism education is one formula to protect students from committing corruption and injustice on earth. The pedagogical element in Surah Luqman, verses 12-19, concerning monotheism education, can be measured by examining the foundation of monotheism education in the Quran, Surah Luqman, verses 12-19. Likewise, it is measured by the objectives of monotheism education, which aim to achieve balanced growth in the total human personality through training the spirit, rational intellect, and feelings and bodily sensitivity. This is placed in the realization of perfect submission to Allah, both individually, in communities, and throughout humanity, and fosters balance in the human personality, not only intellectually but also emotionally and spiritually.